(untitled) (Asian Journal of Medical and Biological Research, 2017)
Contaminated street food has been linked to food-borne illness and food-borne outbreak. Chotpoti is a popular street food in Bangladesh. This study was conducted to identify enteric bacteria in chotpoti sold in different parts of the capital city Dhaka. From July to October, 2012 we purposively selected 18 sites where chotpoti was sold in Dhaka city. From each site we randomly selected six chotpoti stalls for sample collection. At each stall we aseptically collected approximately 100 gm of a combined sample of chotpoti, chili sauce and water used for cleaning utensils. The combined sample was homogenized and was serially diluted in a sterile test tube with normal saline to obtain a dilution up to 10-5. From each test tube 0.1 ml of dilution was plated on to MacConkey and Blood agar plates under aerobic conditions at 37?C for 24 to 48 hours. Bacterial growth was identified by the colonial morphology, Gram stain, and biochemical tests. Of the 108 samples we analyzed, 84 (78%) were contaminated with bacterial pathogens. Among isolated organisms Acinetobacter (66%) was the most dominant followed by Klebsiella spp. (54%), E. coli (3%) and Proteus spp. (0.9%). Two different organisms were present in 47 (44%) samples. In half of the study sites, every sample was contaminated; in only one site bacterial contamination was absent in all samples. Contaminated street food like chotpoti may cause food borne illness and pose risk of food borne epidemics. Further studies are required for quantitative assessment of pathogens to detect potential sources of contamination and to develop interventions that can effectively reduce street food contamination. Asian J. Med. Biol. Res. December 2016, 2(4): 596-602